Sexual and reproductive health and access to Basic Health Units for quilombola women in the Northern Region of Espírito Santo - Araújo Dias, Jerusa; Verly Luciano, Thaís; Cola, João Paulo; Scabelo Galavote, Heletícia; Espinosa Miranda, Angelica (Guará Journal, 2023)
Objective: To describe the characteristics of sexual and reproductive health and access to health services of quilombola women living in the northern region of Espírito Santo. Methods: A cross-sectional, population-based study was carried out with quilombola women between March 2017 and January 2019. Self-declared quilombola women were interviewed face-to-face using a questionnaire with sociodemographic variables, sexual and reproductive health, and access to health services, after being approved by a Research Ethics Committee. Statistical analysis consisted of calculating the mean and standard deviation or median and interquartile range. Fisher’s chi-square test was performed to identify differences associated with place of residence (rural or urban area). Results: Living in rural areas was more frequent among quilombola women with low education, first sexual intercourse under the age of 15, having three or more children, and greater difficulty accessing health services. Conclusion: The results indicated differences in sociodemographic and sexual and reproductive health issues between quilombola women in urban and rural areas. Living in rural areas suggests difficulty in accessing health services. It is necessary to implement public policies targeting the Black population to reduce the structural racism present in our society.